Meat intake and risk of hepatocellular carcinoma in two large US prospective cohorts of women and men. (13th July 2019) - Ma, Yanan; Yang, Wanshui; Li, Tricia; Liu, Yue; Simon, Tracey G; Sui, Jing; Wu, Kana; Giovannucci, Edward L; Chan, Andrew T; Zhang, Xuehong
Abstract: Background: Epidemiological evidence on the associations between meat intake and risk of hepatocellular carcinoma (HCC) was limited and inconsistent. Methods: We prospectively examined the association between consumption of meats and meat mutagens with HCC risk using data from the Nurses' Health Study and the Health Professionals Follow-up Study. Cox proportional-hazards regression models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) after adjusting for known liver-cancer risk factors. Results: During up to 32 years of follow-up, we documented 163 incident HCC cases. The HRs of HCC for the highest vs the lowest tertile intake levels were 1.84 (95% CI: 1.16–2.92, P trend = 0.04) for processed red meats and 0.61 (95% CI: 0.40–0.91, P trend = 0.02) for total white meats. There was a null association between unprocessed red meats and HCC risk (HR = 1.06, 95% CI: 0.68–1.63, P trend = 0.85). We found both poultry (HR = 0.60, 95% CI: 0.40–0.90, P trend = 0.01) and fish (HR = 0.70, 95% CI: 0.47–1.05, P trend = 0.10) were inversely associated with HCC risk. The HR for HCC risk was 0.79 (95% CI: 0.61–1.02) when 1 standard deviation of processed red meats was substituted with an equivalent amount of poultry or fish intake. We also found a suggestive positive association of intake of meat-derived mutagenicity or heterocyclic amines with risk of HCC. Conclusions: Processed red meat intake might be associated with higher, whereas poultry or possibly fish intake might be associated with lower, risk of HCC. Replacing processed red meat with poultry or fish might be associated with reduced HCC risk.